Mechanistic Study on the Oxidation of 4-Hydroxycoumarin by Diperiodatonickelate(IV) in Aqueous Alkaline Medium - Ramesh S. Shettar; Nagaraj P. Shetti; Sharanappa T. Nandibewoor (E-Journal of Chemistry)
The oxidation of 4-hydroxycoumarin (HDC) by diperiodato- nickelate(IV) (DPN) in aqueous alkaline medium at a constant ionic strength of 1.0 mol dm-3 was studied spectrophotometrically at 298 K. The reaction between DPN and 4-hydroxycoumarin in alkaline medium exhibits 1:3 stoichiometry (HDC: DPN). The reaction is of first order in [DPN] and has less than unit order in [HDC] and fractional order in [alkali]. The oxidation reaction in alkaline medium has been shown to proceed via a DPN- 4-hydroxycoumarin complex, which decomposes slowly in a rate-determining step followed by other fast steps to give the products. The main products were identified by spot test, IR, 1HNMR studies. The reaction constants involved in the different steps of the mechanism were calculated. The activation parameters with respect to slow step of the mechanism were computed and discussed and thermodynamic quantities were also determined.